2023
DOI: 10.3390/jcm12113767
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Statistical Shape Model and Assessment of Anatomical Shape Variations in the Hemipelvis

Abstract: Knowledge about anatomical shape variations in the pelvis is mandatory for selection, fitting, positioning, and fixation in pelvic surgery. The current knowledge on pelvic shape variation mostly relies on point-to-point measurements on 2D X-ray images and computed tomography (CT) slices. Three-dimensional region-specific assessments of pelvic morphology are scarce. Our aim was to develop a statistical shape model of the hemipelvis to assess anatomical shape variations in the hemipelvis. CT scans of 200 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…These results were consistent with the SSM in the current study, accounting for variation in the femoral capsular attachments. Studies of pelvis morphology have not found variation in the acetabular geometry (i.e., version and inclination) among the common modes of pelvis variability [58,59]. The current SSM likewise observes minimal variation in acetabular inclination among the dominant shape modes and decreased diameter of the acetabular rim coupled with decreased acetabular version as part of mode 4 (Figure 5 and Table 1).…”
Section: Discussionmentioning
confidence: 44%
“…These results were consistent with the SSM in the current study, accounting for variation in the femoral capsular attachments. Studies of pelvis morphology have not found variation in the acetabular geometry (i.e., version and inclination) among the common modes of pelvis variability [58,59]. The current SSM likewise observes minimal variation in acetabular inclination among the dominant shape modes and decreased diameter of the acetabular rim coupled with decreased acetabular version as part of mode 4 (Figure 5 and Table 1).…”
Section: Discussionmentioning
confidence: 44%